Książki wyzwalają emocje - Żórawska, Natalia (Tematy i Konteksty, 2017)
This article is a review of the book by Ryszard Koziołek entitled Dobrze się myśli literaturą (Literature is a good way of thinking). This publication is a collection of essays in which the literary expert considers the essence of contemporary reading. Koziołek pays special attention to emotions accompanying reading – bot the latest literature and the books considered to be classic ones. He indicates that literature is a special kind of continuity which can be analyzed through the prism of many fields of science, among others, economics or psychology.